PENGARUH PERECANAAN DAN PELAKSANAAN ANGGARAN TERHADAP PENYERAPAN ANGGARAN (STUDI KASUS PADA KECAMATAN BACAN, KECAMATAN BACAN SELATAN DAN KECAMATAN BACAN TIMUR) - Husen, M Aprialdy; Bailusy, Muhsin N; Hadady, Hartaty (Jurnal MS, 2022)
The main objectives of this study were to determine and analyze: the influence of planning on budget absorption in Bacan subdistrict, southern Bacan sub-district and eastern Bacan sub-district; and the influence of the budget on budget absorption in Bacan sub-district, southern Bacan sub-district and eastern Bacan sub-district. Methodology: This study uses multiple linear regression analysis using SPSS version 23 as a statistical test tool. The data collection tools used were questionnaires and interviews, and the number of respondents was 99 respondents spread over the southern Halmahera district. Finding: In the regression output, the significance number for the Planning variable is 0.731. This value is greater than the significance level of 0.05 so that it states that budget planning has no effect on budget absorption and it can be concluded that H1 is rejected because it is supported by the data and is not in accordance with research expectations. At the output of the regression obtained a significant figure for the budget implementation variable of 0.000. This value is smaller than the significance level of 0.05, indicating that budget execution has a positive effect on budget absorption and it can be concluded that H2 is accepted. Conclusion: (1) Planning has no effect on budget absorption in Bacan District, South Bacan District and East Bacan District. It can be seen from the significance figure for the budget planning variable that it is 0.731 because there are still many village officials who have planned or have budgeted for a plan but in implementation it is not realized so that it can weaken the absorption capacity of the budget; and (2) budget implementation has an effect on budget absorption in South Halmahera in Bacan District, South Bacan District and East Bacan District. It can be seen from the significance figure for the budget implementation variable, which is 0.000. Because if the implementation is good, it can absorb the budget itself and vice versa.